2021
DOI: 10.1007/s00115-020-01050-4
|View full text |Cite
|
Sign up to set email alerts
|

Künstliche Intelligenz in der Neurointensivmedizin

Abstract: Künstliche Intelligenz in der NeurointensivmedizinHintergrund Künstliche Intelligenz (KI) verfolgt das Ziel, eine Methode zu entwickeln, um komplexe Sachverhalte auf Basis großer Datenmengen zu erfassen und zu lösen. Möglicherweise werden Computer dadurch das Denken der Menschen erweitern.Als Grundlage für selbstlernende KI bedarf es neben den Methoden des maschinellen Lernens ("supervised machine learning", "unsupervised machine learning" und "reinforcement learning", . Abb. 1; . Tab. 1) folgender Punkte: 4 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…The complexity matrix shown in Table 2 is used to calculate performance metrics (Table 2). 2 True Negative, 3 False Positive, 4 The complexity matrix obtained as a result of the study is shown in Figure 3. In this matrix, each algorithm is classified into 4 different groups as the CTS grade of the algorithm (0 normal, 1 mild, 2 modarete, 3 severe).…”
Section: Simulation Results and Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity matrix shown in Table 2 is used to calculate performance metrics (Table 2). 2 True Negative, 3 False Positive, 4 The complexity matrix obtained as a result of the study is shown in Figure 3. In this matrix, each algorithm is classified into 4 different groups as the CTS grade of the algorithm (0 normal, 1 mild, 2 modarete, 3 severe).…”
Section: Simulation Results and Performance Evaluationmentioning
confidence: 99%
“…2 AI aims to develop a method for capturing and solving complex problems based on large amounts of data. 3 It also has the effect of changing the current model in the diagnosis, treatment, prediction, and economics of neurological diseases. 2 It has been understood that with the use of artificial intelligence, it becomes easier to diagnose permanent neurological damage and even guides the prevention of diseases.…”
Section: Introductionmentioning
confidence: 99%